Stearoyl-Acyl Carrier Protein Desaturase Mutations Uncover an Impact of Stearic Acid in Leaf and Nodule Structure . Issue 3 (1st May 2017) - Lakhssassi, Naoufal; Colantonio, Vincent; Flowers, Nicholas D.; Zhou, Zhou; Henry, Jason; Liu, Shiming; Meksem, Khalid
Abstract : Mutational analysis of SACPD-C reveals an impact of stearic acid accumulation in leaf and nodule structure and morphology. Abstract: Stearoyl-acyl carrier protein desaturase (SACPD-C) has been reported to control the accumulation of seed stearic acid; however, no study has previously reported its involvement in leaf stearic acid content and impact on leaf structure and morphology. A subset of an ethyl methanesulfonate mutagenized population of soybean ( Glycine max ) 'Forrest' was screened to identify mutants within the GmSACPD-C gene. Using a forward genetics approach, one nonsense and four missense Gmsacpd-c mutants were identified to have high levels of seed, nodule, and leaf stearic acid content. Homology modeling and in silico analysis of the GmSACPD-C enzyme revealed that most of these mutations were localized near or at conserved residues essential for diiron ion coordination. Soybeans carrying Gmsacpd-c mutations at conserved residues showed the highest stearic acid content, and these mutations were found to have deleterious effects on nodule development and function. Interestingly, mutations at nonconserved residues show an increase in stearic acid content yet retain healthy nodules. Thus, random mutagenesis and mutational analysis allows for the achievement of high seed stearic acid content with no associated negative agronomic characteristics. Additionally, expression analysis demonstrates that nodule leghemoglobin transcripts were significantly more abundant in soybeans with deleterious mutations at conserved residues of GmSACPD-C. Finally, we report that Gmsacpd-c mutations cause an increase in leaf stearic acid content and an alteration of leaf structure and morphology in addition to differences in nitrogen-fixing nodule structure.